Rebuilding Communitarian and Rural Organizational Forms in the North Region of Costa Rica: A Comparison Between the Development Associations of Aguas Zarcas and La Fortuna During the 1970’s - Villalobos Cubero, Lissy Marcela (2019)
This article presents a comparative perspective about first integral Development Association (ADI) in two comunities of San Carlos (Alajuela): Aguas Zarcas and La Fortuna. The principal idea consisted in elaborated an interpretation of local power relations in these places, the communitary needs, the proyects end them strategies becoming for “building community” in rural area context, during costa rican 1970’s decade.